Analisis Kinerja Seismik Gedung dengan Pushover Analysis (Studi Kasus: Gedung Perkantoran Tiga Tingkat yang Runtuh Akibat Gempa Palu 2018): Building Seismic Performance Analysis with Pushover Analysis (Case Study: Three-level Office Building Collapsed Due to the 2018 Palu Earthquake) - Wardi, Syafri; Ramadhani, Utari (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2023)
Indonesia is an earthquake-prone country. The 2018 earthquake in Palu, Sulawesi, caused significant damage or collapse of the buildings. This research is aimed to evaluate the seismic performance of a three-story office building at Tadulako University and to evaluate what caused the collapse of the building. Evaluation of seismic performance was conducted using the default plastic hinge in SAP2000. The analysis results showed that the plastic hinge occurred first at the end of the beam, followed by the plastic hinge at the end of the column. The performance point from the intersection of the capacity curve and capacity spectrum based on ATC-40 indicated that the performance level of the building was damage control, which means that the building can resist seismic force and has a low risk of human death. These results did not represent the post-earthquake condition in which the building collapsed due to failure of the beam-column joint because the shear reinforcement was not installed in the beam-column joints. Further studies are necessary in order to develop an analysis model, including the failure model of the beam-column joint.